Commentary on Paul Ernest’s Theory about Teachers’ Beliefs and Practice - Milica Videnovic (Indonesian Journal of Mathematics Education, 2021)
In this short communication, the author analyzed Paul Ernest’s theory on relationships between teachers’ beliefs, and their impact on teachers’ practice of mathematics. The author considered the teachers’ espoused and enacted models of mathematics assessment in addition to the teachers' views of the nature of mathematics, teaching, and learning models. The author also considered three purposes of mathematics assessment.